2021
DOI: 10.1177/20406207211048959
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging treatment options in primary mediastinal B-cell lymphoma

Abstract: Previously considered a subtype of diffuse large B-cell lymphoma (DLBCL), primary mediastinal B-cell lymphoma (PMBCL) is now recognized by the World Health Organization as an independent entity. PMBCL has clinicopathologic features that are separate from systemic DLBCL and harbors some biologic characteristics which overlap with nodular sclerosing classic Hodgkin’s lymphoma (cHL). Similar to cHL, copy number alterations of 9p24.1 are frequently seen in PMBCL, which leads to increased expression of key genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Lymphomas of the mediastinum can originate either from the lymph nodes or the thymus. These display similar morphological and molecular features to their counterparts with other locations [84,85].…”
Section: Figure 10 -Hassall's Corpuscle Surrounded By Cells Exhibitin...mentioning
confidence: 63%
“…Lymphomas of the mediastinum can originate either from the lymph nodes or the thymus. These display similar morphological and molecular features to their counterparts with other locations [84,85].…”
Section: Figure 10 -Hassall's Corpuscle Surrounded By Cells Exhibitin...mentioning
confidence: 63%
“…Hopefully, the remarkable results of PD-1/PD-L1 inhibitors in tandem with CD30 antibody-drug conjugates make it a promising immunochemotherapy in the treatment of PMBCL. [42]…”
Section: Discussionmentioning
confidence: 99%
“…These studies have identified the efficacy of PD-1 in PMBCL, especially combined with other agents. Numerous clinical trials assessing combination therapies with immune checkpoint inhibitors are ongoing [145].…”
Section: Primary Mediastinal Large B-cell Lymphoma (Pmbcl)mentioning
confidence: 99%